A Case Report : Pregnancy with Multiple Sclerosis (Ibrahim Cardiac Medical Journal, 2020)
Multiple sclerosis causes disability in young adults and like most autoimmune diseases, affects women more commonly in their child-bearing years. In general, pregnancy does not appear to affect the long-term clinical course of multiple sclerosis and the disease does not affect the course or outcome of pregnancy. In this reportedcase, a pregnant woman with multiple sclerosis showed relapse of the disease in first half of her pregnancy and disease was well controlled in the second half of her pregnancy and postpartum period after taking appropriate measure. Women who have multiple sclerosis and wish to have a family can usually do so successfully with the assistance of their neurologist and obstetrician.Ibrahim Card Med J 2019; 9 (1&2): 93-95